Aplicação do conceito Internet das Coisas (IoT) e plataformas open source para monitoramento de painéis elétricos de baixa tensão - Artur, Matheus Damaceno (2023)
In an increasingly dynamic, complex and competitive market, proper maintenance strategy and maintenance actions are essential for companies to keep their processes and equipment operating safely and reliably, to meet quality requirements and lower overall costs. In this scenario, the implementation of machine condition monitoring solutions plays an important role, and this process is currently considered one of the main levers in global performance research. Inserted in this context, the present work aims to develop a low-cost prototype with the application of an ESP32 microcontroller, open-source software platforms and the concept of IoT (Internet of Things) to cover the functionality of data collection and monitoring of electrical quantities and environmental aspects of an electrical panel in continuous time. Additionally, the use of the Big Data concept for data processing is foreseen, and the construction of a model that generates alerts and provides subsidies for health prognosis, implementation of maintenance/performance indicators and failure prediction. This solution is expected to help companies implement a Condition Based Maintenance (CBM) strategy, make more assertive decisions in maintenance actions, reduce costs in corrective interventions and point out ways for asset management to be more efficient. At first, a prototype was developed with a total cost of US$ 155.99, tests and calibration of the sensors were carried out in the laboratory. Finally, the solution in an industrial environment was applied, in which the following variables were monitored: ambient temperature, relative air humidity, dew point and barometric pressure inside the panel, opening/closing status of the doors of the Motor Control Center (MCC), temperature and operating status of a circuit breaker and contactor, in addition to electrical currents and voltages of 2 motors of the primary wheat milling cylinder bank. The merit of the work can be attributed to the possibility of applying Industry 4.0 concepts to solve real problems and the high potential for scalability.